Blindness and visual impairment due to uncorrected refractive error in sub-Saharan Africa: review of recent population-based studies. Issue 7 (8th February 2012) - Sherwin, Justin C; Lewallen, Susan; Courtright, Paul
Abstract : Aim: The authors aimed to review published data on uncorrected refractive error (URE) as a cause of blindness and visual impairment in adults aged ≥40 years in sub-Saharan Africa (SSA). Methods: Data were extracted from population-based prevalence surveys measuring presenting visual acuity (PVA). Results from 11 surveys performed in 10 countries in SSA, encompassing 39 458 people aged ≥40 years and older, are presented. Results: The prevalence of blindness (PVA<3/60 in better eye) ranged from 1.1% in an urban district of Cameroon to 7.9% in a rural district in Ethiopia. More than half of studies (6/11) reported no blindness due to URE. The proportion of moderate visual impairment (PVA ≤6/60 and >6/18) due to URE ranged from 12.3% to 57.1%. Excluding two studies that included uncorrected aphakia as part of URE, the highest proportion of blindness and severe visual impairment due to uncorrected aphakia was found in Gambia (15.2%) and Nigeria (15.8%), respectively. Conclusion: Although URE is a leading cause of visual impairment, it does not represent a major cause of blindness in SSA.